The One Health Approach: A Critical Pathway for Public Health and Sustainable Development in the Developing World - Thapa Shrestha, Upendra; Joshi, Dev Raj (Tribhuvan University Journal of Microbiology, 2025)
One Health, which views interdependencies between human, animal, and environmental health, is receiving increasing attention across the globe as an effective way to handle the complexities associated with health issues. In developing countries, like Nepal, where the economic survival of human populations is ecologically interwoven with animals, wild animals, and the natural environment, One Health is no longer a theoretical or academic model but the need of the day. Nepal is an exemplary situation for applying the concepts of One Health. There is a large number of people that depend on agriculture and animal resources as a means of living. Direct contact between human and animal populations and minimal biosecurity measures make them vulnerable to incidents of transmitting and acquiring diseases from each other. These include rabies, bird flu, brucellosis, leptospirosis, Q fever, tick-borne viral diseases, and Japanese encephalitis, which continue to threaten the community at large. Furthermore, these diseases continue to have an increased impact on the rural sectors and the commonly deprived sections of the community, thereby worsening the already prevailing disparity between those who are able to access better healthcare and those who are deprived.